Mencintai Diri Penyandang Disabilitas di Indonesia dari Perspektif Albert Camus - Bambang Kuncoro; Ahmad Zubaidi; Misnal Munir (Al-Ulum, 2020)
The focus of this paper is to examine Albert Camus' work on disability. The research method used is library philosophy research with qualitative descriptive characteristics. Camus' works are used as formal objects to analyze material objects, namely people with disabilities in Indonesia. Data analysis was performed by applying methodical hermeneutic elements: interpretation, historical continuity, heuristics, and description. This paper aims to explore the meaning of life for persons with disabilities in Indonesia from the perspective of Albert Camus' philosophy. The findings of this paper, from Camus' philosophy, make disability absurd. In order to have meaning in life, they must face absurd situations through loving themselves. That can be achieved by being self-aware and doing good things for yourself and others. These people use these ethical competencies to carry on the responsibility of doing good things for others.